ENVIRONMENTAL RISK ANALYSIS DUE TO EXPOSURE TO CARBON MONOXIDE (CO) IN THE GORONTALO CITY AREA - Nakoe, Moh. Rivai; S. Lalu, Nur Ayini; Paramata, Arfiani Rizki (UNG, 2024)
Air is necessary for the continuity of creature life, especially man. Air cleaning has benefits, but the most important and foremost thing is For the Respiratory man. Motorized vehicles have the biggest influence on worsening air pollution. The primary pollutants _ contained in exhaust gases in vehicles are carbon monoxide (CO) and particulate dust. Research purposes This knowledge of Carbon Monoxide (CO) concentration Analyzes risk ecological (HQ) consequences of CO exposure, analyzing the grand average exposure ( intake ) and level realtime risk (RQ). Carbon monoxide (CO) exposure is around the Gorontalo City area: Fifth Lake, Front Gorontalo State University campus, and shopping center. Types of research This is an observational study with an approach to Ecological Risk Assessment (ERA) and Health Risk Assessment (HRA) through study field (field studies). Research results show 3 locations are showing Carbon Monoxide (CO) levels have exceeded border brother or standard quality air ambient, with the presentation highest at location three, namely the shopping centers, with results of 39,568 Î¼g /Nm 3. Based on the results, it can be known that CO levels in Gorontalo City are already included in category No safe because 100% of the sample location exceeds the Threshold Limit Value (NAV) based on PP No. 22 of 2021 concerning maintenance Protection and Management Environment for _ value (CO) is 10,000 Î¼g /Nm 3 (10 mg/m 3 ). The calculation results in intake CO exposure realtime big risk health For all locations Good of the CO parameters incl in category risky with RQ 1. People living in the area location taking samples are expected to care more about health and prevention, like getting used to using a mask when working and reducing the habit smoke To minimize exposure to carbon monoxide and TSP.